THE ADOLESCENT HEALTH PROGRAM IN THE OPINION OF THE NURSING TECHNICIANS OF THE FAMILY HEALTH STRATEGY - Sebastião Junior Henrique Duarte; Pollyani Christina Flauzino Albuquerque; Christianne Faria Coelho Ravagnani; Neuci Cunha dos Santos (Universidade Federal do Paraná, 2013)
This study aimed to investigate the opinion of the nursing technicians working in the Family Health teams, regarding the actions undertaken in the Adolescent Health Programs - Education for Work for Health Project / Family Health in Cuiabá in the state of Mato Grosso. The 26 participants in this qualitative study answered a questionnaire with data for socio-demographic characterization and with questions requiring longer answers regarding the Program. The Discourse of the Collective Subject was the theoretical tool for organizing and analyzing the data, which evidenced three central ideas: the organization of the Adolescent Health Program, the difficulty of working with adolescents' health, and the search to overcome the difficulties. Considering that the majority (85%) of the participants mentioned not having received training for working with adolescent health, the need was evidenced for continuous education with a view to qualifying the assistance provided by the nursing technicians.